CHARACTERIZATION OF IRON PRODUCTION FROM MILLS CALE BY CARBOTHERMIC REDUCTION - Lukman Faris Nurdiyansah; Nono Darsono; Deni Shidqi Khaerudini (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Millscale is a large by product of metal factory. Many methods to recycled it to many applications. The aim of this research is recycled millscale to produce the iron by reduction method with graphite as reductant agent. The reduction process was deed by milled millscale and graphite powder with 4:1 weight ratio was by used High Energy Milling with 4, 6, 12 hours milling time variations. The powder then was characterized by X-Ray Diffraction (XRD), Vibrating Sample Magnetometer (VSM) and SEM-EDS test. The XRD test result is Fe3C as a main phase then carbon, magnetite, wustite and Iron as a minor phase. The percentage of iron composition is increase during milling times amount to 6; 10.9; 13 %. The remanence for the 4, 6, and 12 hours of milling time variation, is 2.89, 3.39, and 4.98 emu/g, for the coercivity (Hc) is 209.58, 188.47, and 223.65 Oe and the magnetic saturation number is 22.59, 30.7, 39.15 emu/g, from Hc value it is concluded that the powder has superparamagnetic behavior.  From SEM-EDS is knowed that the distribution of Fe is more uniform on the surface samples with the increase of milling time.